STRESSZ A SZÁMOK MÖGÖTT: A MATEMATIKAI SZORONGÁS ÉS ANNAK HATÁSA AZ ÁLTALÁNOS ISKOLÁBAN - Dudok, Fanni; Forrás, Ágnes (Kultúratudományi Szemle, 2025)
The Stress Behind the Numbers: Mathematical Anxiety and Its Impact in Primary School The study examines the phenomenon of mathematical anxiety among primary school students, highlighting its manifestations, contributing factors, and differences based on age and gender. The research aims to explore the impact of mathematical anxiety on academic performance and attitudes, providing a foundation for pedagogical strategies to reduce anxiety. In the longitudinal study, 92 students from a primary school in a county seat participated by completing a shortened version of the Mathematics Anxiety Scale (MAS-UK) during two measurement phases. Data analysis, conducted through ANOVA and Post Hoc tests, revealed significant differences between groups and grades. Findings indicated a slight decrease in anxiety levels among lower-grade students, while higher-grade students experienced increased anxiety in several situations, particularly during tests and teacher interactions. Girls generally exhibited higher levels of anxiety compared to boys, with the gap widening in higher grades. The study underscores that mathematical anxiety is a complex and multidimensional phenomenon closely linked to age, gender, teaching methods, and the learning environment. The findings highlight the importance of supportive pedagogical practices and differentiated teaching strategies, which can help reduce anxiety and foster positive attitudes toward mathematics among students.